2018
DOI: 10.1016/j.jeem.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Output-based allocations in pollution markets with uncertainty and self-selection

Abstract: We study pollution permit markets in which a fraction of permits are allocated to firms based on their output. Output-based allocations, which are receiving increasing attention in the design of carbon markets around the world (e.g., Europe, California, New Zealand), are shown to be optimal under demand and supply volatility despite the output distortions they may create. In a market that covers multiple sectors, the optimal design combines auctioned permits with output-based allocations that are specific to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…(15) s = tē y , 12 Gersbach and Requate (2004) use this setup in the competitive version of their model. Meunier et al (2018) explore situations without budget balance and under uncertainty. 13 See Fischer (2011) and Sterner and Isaksson (2006) for a model of an OBR system where strategic manipulation of the total emission revenues is discussed.…”
Section: Expenditure-based Refunding (Ebr)mentioning
confidence: 99%
“…(15) s = tē y , 12 Gersbach and Requate (2004) use this setup in the competitive version of their model. Meunier et al (2018) explore situations without budget balance and under uncertainty. 13 See Fischer (2011) and Sterner and Isaksson (2006) for a model of an OBR system where strategic manipulation of the total emission revenues is discussed.…”
Section: Expenditure-based Refunding (Ebr)mentioning
confidence: 99%
“…In such a case the two OBA rates will differ from the leakage rates because OBA rates play an additional role now. As documented by Meunier et al (2016), they also offer the possibility to partially index the total cap to actual realization of demand, which vary period after period. However, this indexing comes at a price since the introduction of a wedge between OBA and leakage rates introduces an inefficiency.…”
Section: Optimal Design Under Uncertaintymentioning
confidence: 99%
“…We shall address this question building on a recent paper of the authors (Meunier et al, 2016) in which it is demonstrated that, even in absence of leakage, there are good reasons to introduce OBA for sectors subject to large demand and supply shocks. From a welfare point of view, in absence of leakage but with uncertainty, the impact of using OBA can be understood using the price versus quantity framework introduced by Weitzman (1974).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as we show in this paper (Section 3.3), cumulative emission reductions due to national coal phase-out policies in the period 2021-2030 are in the order of 1 Gt CO 2 e. A significant allowance surplus would therefore develop if the cap is not adjusted to reflect this emission reduction due to interacting policies. The literature has developed a variety of proposals on how to maintain scarcity in the EU ETS, from delegating cap setting power to an independent authority akin to a central bank (De Perthuis & Trotignon, 2014) to introducing a price collar (Fuss et al, 2018) and flexibility in the cap (Meunier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%